Android-Based Cryptography Applications Using The Rail Fence Cipher Algorithm - Raden Diky Zailani; Khairil Khairil; Abdussalam Al Akbar (Jurnal Media Computer Science, 2023)
Android-based cryptographic applications using the rail fence cipher algorithm are made using the Java programming language (AndroidStudio), the PHP programming language (JSON File Web Service) and the MySQL database. This application has a url link for storing PHP files and message data in the database, while the url link is http://railfencecipher.my.id/. An Android-based cryptographic application using the rail fence cipher algorithm has been uploaded to Google Playstore by entering the rail keyword fence cipher. An android-based cryptographic application using the rail fence cipher algorithm can be used to assist communication between the two parties, both the sender and the recipient of the message. In addition, this application has implemented a rail fence cipher algorithm that is used to maintain the confidentiality of the message stored in the application's database. The records in the message body column in the database are in random form, therefore they cannot be read. This of course makes the application maintain the confidentiality of the messages sent, because there is a process of scrambling (encryption) of the message. Based on the results of the tests that have been carried out, the functionality of the android-based cryptographic application using the rail fence cipher algorithm runs well as expected and the message sent between the recipient and the sender is kept confidential because the message is encrypted.